THE ROLE OF PEDAGOGICAL VALEOLOGY IN IMPROVING THE WORKING CAPACITY OF STUDENTS AND PREVENTING THEIR FATIGUE (EDUCATION IN THE 21ST CENTURY, 2023)
The great scientific and technical discoveries of the 21st century, the unprecedenteddevelopment of information technologies and their integral part of public life, seem to havecontributed to the fact that humanity has become more civilized and prosperous. However, inreality, on the way of their progress and development, people have faced a number of problemsand challenges that threaten their normal life, deserve attention and require urgent solutions.Pedagogical science of health (pedagogical valeology), as one of the directions of health science,deals with the coverage of the above-mentioned problem, studying the issues of education andupbringing of a person with a healthy lifestyle. This is considered one of the greatest values thatmust be maintained and improved from the very first days of life. The preservation andstrengthening of students ' health, education and upbringing of a healthy person is one of the mostimportant tasks of pedagogical valeology, since the progress and strength of the state and societyare determined by the health of each of its members, which will contribute to the progress,development and enrichment of intellectual potential.In the modern world, rapid development of information technologies, increasing complexityof educational programs and overcrowding often lead to poor health of students, and sometimeseven to a decrease in interest in learning.In connection with the above-mentioned problem, in this article we used the problem ofpreserving the health of the younger generation as a guarantee of a strong state and the progress ofsociety.
Keywords: Healthy lifestyle, pedagogical health education, valeological culture, valeological education, valeological behavior, motor activity, hygiene rules